If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -18 = 40 + 3x Reorder the terms: -18 + 9x = 40 + 3x Solving -18 + 9x = 40 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -18 + 9x + -3x = 40 + 3x + -3x Combine like terms: 9x + -3x = 6x -18 + 6x = 40 + 3x + -3x Combine like terms: 3x + -3x = 0 -18 + 6x = 40 + 0 -18 + 6x = 40 Add '18' to each side of the equation. -18 + 18 + 6x = 40 + 18 Combine like terms: -18 + 18 = 0 0 + 6x = 40 + 18 6x = 40 + 18 Combine like terms: 40 + 18 = 58 6x = 58 Divide each side by '6'. x = 9.666666667 Simplifying x = 9.666666667
| 7-12x/4 | | 2x+3x+9=8 | | 6x^2+28x+26=0 | | 10=-12-e | | (7x+13)+(7x-2)= | | -2(y-3)=y+4s | | 20x=-80 | | -6y^2=-54 | | [-4g+2]=8 | | -4(6r-7)=35 | | (54x+65y)+(-11x+45y)= | | 4x+44=-19+x | | 3(x+5)=2(2x+11) | | (2x-5)(x-7)=0 | | 6(4w+8)=8 | | 10x+10=-40 | | X-9(3-x)=5+10x | | -7(2t+10)=-42 | | 8(2-p)=27 | | 3(f-9)=-30 | | (14x+6y)+(48x+34y)= | | 6+55x=44x+9 | | 8w+4x=5w-6x | | -4a+7=-17 | | [-5x-2]=8 | | 3*x-18=(x+3)*(x-3)*2+x^2+3*x+9 | | (50x+51y)-(-29x+3y)= | | -3(2x+9)+9= | | 12t-5=12t+5 | | X^5-2x^4+4x^2-5x+5= | | 19/5+5y=10y-1/5 | | 4*x+x=88 |